Minima Onomastica Graeca Alpharabia: Notes on the Treatise "Tafsir Asma Al-Hukama" - Younesie, Mostafa (Collectanea Philologica, 2021)
One of the treatises attributed to the scholar and philosopher al-Farabi is the fascinating single- page manuscript entitled tafsir asma al-hukama, a small document containing a shorthand inventory of fourteen Greek names. Although the authenticity of the attribution is still debated, the treatise itself demonstrates that its author had a strong interest in the interplay of philology and philosophy – a theme that first appears in a remarkable passage in Plato’s Politeia, namely Book IX, 582e. This paper therefore will examine the nature of the tafsir asma al-hukama, especially with regard to the title, which I leave untranslated until the last part of the paper, since the exact meaning of the words in the title forms a major part of my argument. Although the tafsir asma al-hukama is seemingly a very minor text, I believe that it represents a fascinating moment in the history of the dialogue between philology and philosophy. The result of my examination, then, will be a kind of maxima in minimis or hologram on a minor scale. I shall begin with a discussion of the importance of ism in al-Farabi.